Gambaran Proses Kelompok Pelaku Bullying di Salah Satu Sekolah Percontohan Anti-bullying di Jakarta - Setiawie, Yudhi; Gunawan, William (Noetic Psychology, 2010)
The purpose of this study was to see how the image of the group in one of the authors of acts of intimidation against intimidation of the pilot school in Jakarta. Process in the middle in this discussion group is a study of interaction between individuals within a group of attitudes and behavior of mutual influence each other as part of the group relations. This study focuses on the stages of team development model put forward by (Tuckman & Jensen). There are five basic stages of group formation, including the steps establishment stage (stage forming), (stage Storming), (stage Norm), (stage performing) and the final stage group (suspending phase) that exists in the interaction. Interconnected to form patterns that affect the process of group formation. By using a model of group development stage, it will be on explaining the various activities that occur at each stage of group formation, so it will be visible with a clear description of the stages of the process of forming groups of perpetrators of bullying in the school environment. Results of research conducted on the basis of qualitative approaches focus group discussions (FGD). The study involved a group of 10 individuals perpetrators of bullying as a subject of research. A selected group of subjects was based on the fact that they have committed acts of bullying behavior toward students class named